CRITICAL THINKING SKILLS LEVEL OF MEDICAL STUDENTS: STUDY IN PRIVATE FACULTY OF MEDICINE - Octaviara Permatasari, Tissa; Pujo Laksono, Nugroho; Akturusiano, Binto (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Critical thinking skill is important for college graduates, especially in applying science to their field of expertise. Therefore, every higher education institution must facilitate the learning of critical thinking skills. In medical education, critical thinking skill include in one of primary competence which is “self-awareness and life- long learning”, which has to be achieved by every medical student. Measurement of critical thinking skill in medical students is important, therefore this study aimed to describe the critical thinking level of medical students at Universitas Swadaya Gunung Jati. This was a descriptive observational study with cross-sectional design. The sample size was 239 medical faculty students at Universitas Swadaya Gunung Jati. Data collection used questionnaire instrument which has been validated. High level of critical thinking skill was dominated by the 2017 batch, both in measuring critical thinking skills level of knowledge, understanding, application, and analysis. Batch of 2018 has good critical thinking skill in the application level. Batch of 2019 has good critical thinking skill in the analysis level. Batch of 2020 has good critical thinking skill in the knowledge level. Medical students at Universitas Swadaya Gunung Jati have good level of critical thinking skills.